ANALISIS PEMAHAMAN KONSEP MATEMATIKA SISWA DALAM MENYELESAIKAN SOAL CERITA MATERI TRIGONOMETRI BERDASARKAN TEORI BLOOM - Fengky Henrixzon Manik; Agung Hartoyo; Romal Ijuddin (Universitas Tanjungpura, 2021)
AbstractThis study aims to describe students understanding of mathematical concepts basedon Bloom's theory in solving trigonometric material story problems in class X SMASanto Fransiskus Asisi Pontianak. Based on Bloom's theory, students have anunderstanding of the concept if they have three indicators of ability. The threeindicators are translation, interpretation and extrapolation. This study uses adescriptive method with a case study research form. Data collection used storyquestions with trigonometric material and interview guideline sheets. The subjects inthis study were students of class XI MIPA at SMA Santo Fransiskus Asisi Pontianakin the 2018/2019 academic year who had studied the trigonometric comparisonmaterial on right triangles. Based on the results of the study, it can be concludedthat in general students have a very poor understanding of the concept based onBloom's theory. This is because students have not been able to fulfill the threeaspects of understanding the concept according to Bloom, where the translationindicator is in the poor category with a percentage of 54.69%, interpretationindicators and extrapolation indicators are in the very poor category with apercentage of 25.69% and 20.83% respectively.Keywords: Bloom's Theory, Story Problems, Trigonometric, Understanding TheConcept